PELATIHAN STRATEGI PEMASARAN DAN PENGUATAN BRANDING DALAM MEMBANGUN USAHA DI LINGKUNGAN KECAMATAN BANDUNG KAB. SERANG - Wijaya, Aden; Meida, Tiara Asti; Hidayatullah, Arip; Maulana, Alif (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This Community Service (PKM) program aims to improve the skills of the Bandung District, Serang Regency, community in developing businesses through marketing strategy training and branding strengthening. The main challenges faced by the local community are a lack of understanding of effective marketing strategies and the suboptimal application of branding concepts in promoting local products. The program's implementation methods included field observation, outreach, interactive training, and ongoing mentoring. The training focused on digital marketing strategy planning, social media management, brand identity creation (logos, slogans, and product packaging), and creative promotional techniques. The results of the program demonstrated an increase in participants' understanding and skills in designing marketing strategies and building strong brand images for their products. Furthermore, participants demonstrated high enthusiasm and commitment to applying the knowledge gained in developing their respective businesses. Thus, this PKM program contributes to increasing the competitiveness and economic independence of the community in Bandung District, Serang.